How can African agriculture adapt to climate change: Perceptions of stakeholders on climate change and adaptation strategies in Ethiopia - Admassie, Assefa; Adenew, Berhanu; Tadege, Abebe (International Food Policy Research Institute, 2008)
The potential adverse effects of climate change on Ethiopia's agricultural sector are a major concern, particularly given the country's dependence on agricultural production. Securing Ethiopia's economic and social well-being in the face of climate change requires that policymakers and stakeholders work together to integrate climate change adaptation into the country's development process. Three stakeholder discussion forums held in 2006 in Addis Ababa, Awassa, and Bahir Dar as part of the project, Food and Water Security under Global Change: Developing Adaptive Capacity with a Focus on Rural Africa, were attended by representatives of the government, civil society, business sector, and local communities. The forums elicited information to enable policymakers to make more informed decisions related to climate change adaptation. The forums complemented ongoing efforts to develop the National Adaptation Program of Action (NAPA), which is overseen by a steering committee representing government, nongovernment, academic, and research institutions. Under NAPA, multidisciplinary technical working groups have been formed to assess the country's vulnerability to the adverse consequences of climate change, gauge current adaptation efforts, and identify ways in which public agencies could assist in minimizing the adverse impacts of climate change. In addition, two national and eight regional workshops were conducted involving nearly 500 participants with various areas of expertise. Like the stakeholder forums, the workshops solicited information to create greater awareness of climate change, assess the extent of the area's vulnerability, and help identify adaptation options. This brief is based on a paper that presents findings from the stakeholder discussion forums, as well as NAPA's technicalworking groups and workshops. These meetings explored stakeholders' perceptions of vulnerability to climate change and considered ways in which adaptation measures could be further integrated into Ethiopia's development process.